2016
DOI: 10.4081/jlimnol.2016.1433
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemistry and trophic state change in a large reservoir in the Brazilian northeast region under intense drought conditions

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 24 publications
0
24
0
3
Order By: Relevance
“…limnetica/Pl. minor, were mainly associated with reduced phosphate-P supply in phase I, which could be due to the strong thermocline in this period (see Santos et al, 2017). Corroborating this condition, Pl.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…limnetica/Pl. minor, were mainly associated with reduced phosphate-P supply in phase I, which could be due to the strong thermocline in this period (see Santos et al, 2017). Corroborating this condition, Pl.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the results of spatial and temporal dynamics of the phytoplankton community in the Castanhão reservoir along the years of 2012 and 2013, when the volume of the reservoir progressively decreased from 70% to 50% (Santos et al, 2017), showed a tendency of temporal rather than spatial variation across the zones. In general, the study period could be divided in three phases based on the phytoplankton structure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations